Neoliberal Indigenous Policy: Settler Colonialism and the "Post‐Welfare" State. (September 2016) - Rowse, Tim
Abstract : Neoliberal Indigenous Policy: Settler Colonialism and the "Post‐Welfare" State. By Elizabeth Strakosch (Houndsmills and New York: Palgrave Macmillan, 2015), pp. vii + 213, with index, £60.00 (cloth).